2015
DOI: 10.31768/2312-8852.2015.37(1):48-52
|View full text |Cite
|
Sign up to set email alerts
|

Cd8 and Cd45ro T Lymphocytes in Bone Marrow of Gastric Cancer Patients: Correlation With Disseminated Tumor Cells and Disease Outcome

Abstract: Aim: To evaluate the association between the presence of CD8 and CD45RO T lymphocytes in bone marrow (BM), disseminated tumor cells (DTCs), tumor hypoxia and their impact on disease outcome. Material and methods: 91 naïve gastric cancer (GC) patients were enrolled into the study. DTCs, CD8- and CD45RO-positive T lymphocytes in BM were detected using immunocytochemistry. All patients were thoroughly informed about the study that was approved by the local ethics committee. Statistical analyses were done using NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…At the same time the association between pre sence of CD8 and CD45RO T lymphocytes and survival was shown: high density of CD8 + and CD45RO + T cells in primary tumor or high density of CD8 + and CD45RO + T cells in bone marrow are the most favorable for patients. These data may allow to consider intratumoral CD8 and CD45RO T lymphocytes as a "keeping factor" that prevents the exit of tumor cells from primary node, dissemination in the circulation and hit into the distant organs, in particular bone marrow, and allow to assume that tumor cells in bone marrow may be existed in a dormant state through the control by T cells in particular by CD8-positive T cells [63,64].…”
Section: Minimal Residual Diseasementioning
confidence: 99%
“…At the same time the association between pre sence of CD8 and CD45RO T lymphocytes and survival was shown: high density of CD8 + and CD45RO + T cells in primary tumor or high density of CD8 + and CD45RO + T cells in bone marrow are the most favorable for patients. These data may allow to consider intratumoral CD8 and CD45RO T lymphocytes as a "keeping factor" that prevents the exit of tumor cells from primary node, dissemination in the circulation and hit into the distant organs, in particular bone marrow, and allow to assume that tumor cells in bone marrow may be existed in a dormant state through the control by T cells in particular by CD8-positive T cells [63,64].…”
Section: Minimal Residual Diseasementioning
confidence: 99%
“…It was shown that CD45RO + -T cells infiltrating into gastric cancer tissues are functional and have significant prognostic value in human gastric cancer [15]. Moreover the presence of CD8-and CD45RO-positive T cells in bone marrow (BM) of gastric cancer patients demonstrated better overall survival than those with the absence of CD8-and CD45RO-positive T cells in BM [16]. At the same time as it was noted by Mei et al [17], the prognostic value of TILs in gastric cancer remains controversial because of the limited number of studies.…”
Section: Introductionmentioning
confidence: 99%